2013
DOI: 10.1017/s1368980013001146
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants of diet quality of the EU elderly: a comparative analysis in four countries

Abstract: Objective: To investigate the sociodemographic determinants of diet quality of the elderly in four EU countries. Design: Cross-sectional study. For each country, a regression was performed of a multidimensional index of dietary quality v. sociodemographic variables. Setting: In Finland, Finnish Household Budget Survey (1998 and; in Sweden, SNAC-K (2001SNAC-K ( -2004; in the UK, Expenditure & Food Survey (2006-07); in Italy, Multi-purpose Survey of Daily Life (2009). Subjects: One-and two-person households of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 19 publications
(23 reference statements)
6
54
0
9
Order By: Relevance
“…Furthermore, this study confirm findings from other studies showing that sociodemographic determinants are associated with diet quality [33] and social relationships are linked to dietary behavior [34]. Conklin and colleagues [34] found that being single or widowed was associated with lower scores on vegetable variety, and the associations were enhanced when combined with male gender, living alone or infrequent friend contact.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, this study confirm findings from other studies showing that sociodemographic determinants are associated with diet quality [33] and social relationships are linked to dietary behavior [34]. Conklin and colleagues [34] found that being single or widowed was associated with lower scores on vegetable variety, and the associations were enhanced when combined with male gender, living alone or infrequent friend contact.…”
Section: Discussionsupporting
confidence: 89%
“…The foundations of norms and values regarding food culture, traditions and eating habits are laid early (Edfors & Westergren, 2012). However, food choice is not static and may change during the course of life so that the eating habits of an individual may not be the same in early adulthood as they are in later life (Mattsson Sydner, 2002;Irz et al, 2014). These changes over time also create variations in food habits between different generations, both with regard to food choice as such, as well as with regard to how the meal as a whole is constructed (Mattsson Sydner, 2002).…”
Section: Food Preferences Are Influenced By Previous Experiences and mentioning
confidence: 99%
“…Maintenance of a healthy diet is one of the most important factors affecting food choice among older consumers and eating healthy can be regarded as an investment to ensure independency (Lundkvist, Fjellström, Sidenvall, Lumbers, & Raats, 2010). Insufficient resources are however, according to Irz et al (2014), not a driver for poor dietary choices in Sweden and Finland. Thus, there is no common diet that suits the needs and wishes of all elderly people but a few recent studies indicate some general features that can be attributed to food for the elderly from a cultural and geographic context.…”
Section: Food Preferences Are Influenced By Previous Experiences and mentioning
confidence: 99%
“…Furthermore, another study reported low dietary quality levels for European elders (29) . This therefore highlights that sociodemographic differences in dietary profile should be considered when designing health and nutrition initiatives.…”
Section: Discussionmentioning
confidence: 99%